Socio-economic Factors Influencing Technology Adoption among Fishermen Operating Motorized Fishing Craft - Balasubramaniam, S.; Charles Jeeva, J.; Ashaletha, S. (Fishery Technology, 2025)
In Kerala, there are about 1.90 lakh active marine fishermen operating about 14 151 motorized fishing craft. The investment pattern, number of fishing days, fuel utilization and technological changes in the motorized fishing sector during the recent years indicate the extent of investment on fishing units, the relationship between the extent of adoption of technologies and the corresponding annual income. This paper presents the results of a study conducted among random samples of 33 fishermen respondents in Thiruvananthapuram district and 31 fishermen respondents in Alappuzha district operating 8.4 m LOA motorized FRP craft. It is seen that monofilament gillnets for mackerel, sardine and other were mostly operated by the fishermen in the FRP craft. Single day fishing was practised and night fishing was not undertaken by these respondents. The adoption behaviour scores explained the extent of adoption of various improved practices/technologies and the variables influencing the technology adoption were determined in the multiple regression analysis. The constraints such as poor landing centre facilities, inadequate kerosene subsidy, inadequate developmental/extension schemes, ever-increasing maintenance costs, diminishing fish catches, ever-increasing fuel prices, occasional conflicts with the mechanised boat operators, ineffective insurance coverage, damages caused to the fishing gears by puffer fishes, inadequate relief measures during natural calamities, financial constraints and excessive fishing capacity were reported as factors inhibiting the adoption of sustainable fishing practices.